2015
DOI: 10.15252/embj.201490899
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional repression by MYB 3R proteins regulates plant organ growth

Abstract: In multicellular organisms, temporal and spatial regulation of cell proliferation is central for generating organs with defined sizes and morphologies. For establishing and maintaining the postmitotic quiescent state during cell differentiation, it is important to repress genes with mitotic functions. We found that three of the Arabidopsis MYB3R transcription factors synergistically maintain G2/M-specific genes repressed in post-mitotic cells and restrict the time window of mitotic gene expression in prolifera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
226
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 128 publications
(236 citation statements)
references
References 68 publications
8
226
2
Order By: Relevance
“…First, we found the strong tendency of the late cell cycle genes to be downregulated in myb3r1/4 (loss of activators) and upregulated in myb3r1/3/5 (loss of repressors). 9,10 However, there were only small numbers of late cell cycle genes that are affected in both myb3r1/4 and myb3r1/3/5 (Fig. 1A).…”
Section: Activator and Repressor Myb3rs: Coordination Rather Than Commentioning
confidence: 99%
See 4 more Smart Citations
“…First, we found the strong tendency of the late cell cycle genes to be downregulated in myb3r1/4 (loss of activators) and upregulated in myb3r1/3/5 (loss of repressors). 9,10 However, there were only small numbers of late cell cycle genes that are affected in both myb3r1/4 and myb3r1/3/5 (Fig. 1A).…”
Section: Activator and Repressor Myb3rs: Coordination Rather Than Commentioning
confidence: 99%
“…8,9 We have recently shown that the other members of MYB3Rs, MYB3R3 and MYB3R5, in Arabidopsis act as transcriptional repressors. 10 Interestingly, MYB3R1, which has redundant function with MYB3R4 activator, 8 has also overlapping repressive function with MYB3R3/5 repressors. This led to unexpected conclusion that MYB3R1 has a dual role in activating and repressing the late cell cycle genes.…”
mentioning
confidence: 99%
See 3 more Smart Citations